2021
DOI: 10.3390/pathogens10070837
|View full text |Cite
|
Sign up to set email alerts
|

3D Cocultures of Osteoblasts and Staphylococcus aureus on Biomimetic Bone Scaffolds as a Tool to Investigate the Host–Pathogen Interface in Osteomyelitis

Abstract: Osteomyelitis (OM) is an infectious disease of the bone primarily caused by the opportunistic pathogen Staphylococcus aureus (SA). This Gram-positive bacterium has evolved a number of strategies to evade the immune response and subvert bone homeostasis, yet the underlying mechanisms remain poorly understood. OM has been modeled in vitro to challenge pathogenetic hypotheses in controlled conditions, thus providing guidance and support to animal experimentation. In this regard, traditional 2D models of OM inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…On the contrary, Tgf-β (a reported repressor of Ptx3 transcription) decreased over time. In the conditioned medium of the 3D cocultures, TNF-α was not detected, while PTX3 and OPG levels were stable over time ( 79 ). Importantly, the expression of selected osteogenic (Bmp2, Alp, Spp1), and antioxidant (Nrf-2, Ho-1) genes were substantially affected by the applied 3D setting, indicating matrix-dependent effects on osteoblasts during an S. aureus infection ( 79 ).…”
Section: Osteoblasts As Inflammatory Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Tgf-β (a reported repressor of Ptx3 transcription) decreased over time. In the conditioned medium of the 3D cocultures, TNF-α was not detected, while PTX3 and OPG levels were stable over time ( 79 ). Importantly, the expression of selected osteogenic (Bmp2, Alp, Spp1), and antioxidant (Nrf-2, Ho-1) genes were substantially affected by the applied 3D setting, indicating matrix-dependent effects on osteoblasts during an S. aureus infection ( 79 ).…”
Section: Osteoblasts As Inflammatory Cellsmentioning
confidence: 99%
“…3D models that closely resemble the in vivo conditions have been implemented ( 79 , 102 , 103 ). In this regard, manufacturing of bioactive bone mimetic scaffolds that recapitulate texture and chemistry of the natural bone matrix provide unique experimental tools to study the interface between pathogens (including S. aureus ) and both skeletal and immune cells in a tightly controlled setting.…”
Section: Limitations Of In Vitro and In ...mentioning
confidence: 99%
“…A number of 3D in vitro culture systems have been developed to study the interactions between bacteria and cells [ 14 ]. S. aureus infection in skin tissue and bone has been studied using 3D co-culture models [ 15 , 16 ]. Ding et al demonstrated that macrophages can transmigrate across a polyethylene terephthalate membrane to reach the epithelial cell layer cultured with S. aureus [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic and prolonged infections with S. aureus represent the highest burden of disease, with decreasing likelihood of treatment success as the infection becomes established [ 23 ]. In this Special Issue, two different publications [ 24 , 25 ] showed the potential of 3D models in gaining more insight towards controlling the burden caused by such a threatening pathogen. Hofstee et al [ 24 ] showed that staphylococcal abscess communities cause myeloid-derived suppressor cell (MDSC) expansion from bone marrow cells and identified possible mediators to be targeted as an additional strategy for treating chronic S. aureus infections.…”
mentioning
confidence: 99%
“…Hofstee et al [ 24 ] showed that staphylococcal abscess communities cause myeloid-derived suppressor cell (MDSC) expansion from bone marrow cells and identified possible mediators to be targeted as an additional strategy for treating chronic S. aureus infections. Parente et al [ 25 ] developed a 3D model of osteomyelitis (OM), a bone condition primarily induced by S. aureus infections, based on co-cultures of S. aureus and murine osteoblastic MC3T3-E1 cells on magnesium-doped hydroxyapatite/collagen I (MgHA/Col) scaffolds that closely recapitulate the bone extracellular matrix. This model shows great potential for the study of OM caused by S. aureus infections.…”
mentioning
confidence: 99%